El Programa Espacial Japonés (1954-2003). - Moncada Andrade, Ricardo (Humania del Sur: Revista de Estudios Latinoamericanos, Africanos y Asiáticos)
The Japanese Space Program represents a unique case in contemporary space history, having developed within a pacifist framework and in close collaboration with the United States, without fully integrating into the military logic of the Cold War. We analyze its evolution between 1954 and 2003, from the creation of the AVSA to the emergence of JAXA. Three distinct phases can be identified: the scientific-academic origins, institutional consolidation, and the crisis of the 1990s that led to its unification. The study demonstrates that Japan’s trajectory was marked by tensions between technological autonomy, external dependence, bureaucratic fragmentation, and civil and strategic objectives.